Pengurangan Sampah Menggunakan Metode Kuantitatif Pada Suku Dinas Lingkungan Hidup Kota Administrasi Jakarta Barat - Jati Prasetiyo; Muhamad Ryansyah; Priatno (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2022)
Jakarta is an urban area in Indonesia that has many environmental problems. Environmental awareness is needed in an effort to solve environmental problems. Environmental awareness in oneself can be formed by the level of environmental knowledge. The Clean environment program is implemented through the Adiwiyata program. The aim of the Adiwiyata program is to encourage and create about the environment and have an environmental culture. Waste reduction is an inseparable part of human life. The problem that must be considered is that basically all humans produce waste and the increased volume of waste disposal is not proportional to the increasing level of human consumption. The solution to this problem is to use descriptive quantitative methods in reducing waste in the urban environment. The results of this study aim to try to change the mindset of people who still use the collect transit waste system.